The Influence of Stigma and Family Support on Long-Term Outcomes of Schizophrenia Patients: A Literature Review - Andi Bulqis Khaerunnisa; Ilma Khaerina; Wirasto Ismail; Irmasanty Irmasanty; Fanny Wijaya (ScieClouds Publishing, 2026)
Schizophrenia is a chronic and severe mental disorder that significantly affects patients’ quality of life, social functioning, and long-term recovery. In addition to biological factors, psychosocial factors such as family support and stigma play crucial roles in determining treatment outcomes and recovery trajectories among individuals with schizophrenia. This study aimed to examine the influence of family support and stigma on the long-term outcomes of patients with schizophrenia through a narrative review of the existing literature. A narrative literature review was conducted using articles retrieved from PubMed, Google Scholar, ScienceDirect, ResearchGate, and Gale. The search employed keywords related to schizophrenia, stigma, family support, long-term outcomes, and mental health. Studies published in English and Indonesian that examined the relationship between family support, stigma, and outcomes among individuals with schizophrenia were included. Following the screening and eligibility assessment process, 20 studies met the inclusion criteria and were analyzed using a narrative synthesis approach. The review revealed that family support is consistently associated with improved quality of life, better medication adherence, reduced relapse rates, increased treatment motivation, and enhanced psychosocial functioning among patients with schizophrenia. Conversely, stigma was found to negatively affect psychological well-being, resilience, caregiving capacity, treatment engagement, and quality of life. The findings further indicated that supportive family environments may mitigate the adverse effects of stigma by promoting acceptance, emotional stability, and social integration. Structured family involvement was also shown to improve clinical and functional outcomes. Family support and stigma are important psychosocial determinants of long-term outcomes in schizophrenia. Strengthening family involvement and implementing stigma-reduction strategies should be considered essential components of comprehensive and recovery-oriented mental health care for individuals living with schizophrenia.